Exploring the feasibility of implementing the P-PD approach in pastoral areas: Assessment in the Somali region of Ethiopia - Habermann, Birgit; Worku, Tigist (International Livestock Research Institute, 2024)
Positive deviance refers to individuals or groups of livestock keepers achieving better outcomes than their peers with similar resources in livestock management in terms of securing livelihoods and overcoming the impact of climate change. Positive deviance is a well-researched field of study emerging from public health research, originally in SE Asia (Zeitlin 1991, Marsh, Schroeder et al. 2004, Lapping, Marsh et al. 2016).